Frictional properties of non-welded and welded fractures in granite - Shen, Linyue (2018)
The purpose of this study is to conduct direct shear tests on welded and non-welded fractures and find the effect of the cementation and roughness for rock stability. Prior to the direct shear test, all the rock samples are scanned by 3D scanner to get the surface roughness profile. Four specimens are prepared to be conducted in the direct shear test, and each of them is tested under 4 different normal loads. Residual friction angle of 35.5o is obtained based on direct shear test on a smooth joint. Based on previous study, the friction angle of dry granite varies from 26o to 38o. For welded joints, the results show that the shear strength is increased by the cementation. Comparing the test results of smooth and rough joints, the roughness is positively correlated with the shear strength.